Distinct and untamed: articulating bulimic identities - Eli, K (Springer Verlag, 2017)
Bulimia nervosa and anorexia nervosa are inextricably linked, with substantial clinical and epidemiological overlaps. Yet, while anorexia has been analyzed extensively in medical anthropology, bulimia remains under-theorized. This is, perhaps, because, compared to self-starvation, binge eating presents a logic of practice that is difficult to reconcile with culturally reified notions of self-control, transcendence, and hard work. Thus, although anthropologists have analyzed anorexic subjectivities as imbued with a sense of cleanliness and purity, moral superiority, and heroics, similar analyses have not been extended to bulimic subjectivities; instead, bulimia has been subsumed, as a tangential disorder, into analyses of anorexia. In this paper, I aim to move bulimic identities from the margins to the centre of anthropological analysis. Based on participant narratives, I analyze bulimic identity as articulated by six Israeli women who identified as bulimic and received treatment for bulimia. The women’s narratives show that bulimic identity is aligned with concepts of distinct selfhood. For these women, to be bulimic was to be framed as ‘abnormal’; but this ‘abnormality’, albeit a source of social stigma and shame, held meanings that went beyond pathology. Through the claiming of bulimic identity, the women positioned themselves as untamed, non-conforming subjects, who acted against gendered and classed expectations—and even against the limitations of the body. Their constructions of bulimic distinction highlight the need for anthropological work that situates bulimia not as a footnote to anorexia, but as a structurally and culturally meaningful condition in its own right.